PENGARUH PENERAPAN PRINSIP-PRINSIP GCG PADA KINERJA KEUANGAN LEMBAGA PERKREDITAN DESA KABUPATEN GIANYAR, PROVINSI BALI - Krismaya Dewi, Kadek (E-Jurnal Akuntansi, 2014)
GCG is a basic principle of good corporate governance , where the application is expected to be used as guidelines in managing the company's good management by taking into account the interests of stakeholders . Village Credit Institutions also need to apply the principles of good corporate governance to improve performance or achieve the title of "Sehat" is given through CAMEL ratio analysis . The purpose of this study was to determine the effect of corporate governance on financial performance LPDs in Gianyar regency , Bali province . This study used a survey method with a questionnaire technique . The samples are 73 LPD and each one taken from each respondent contained LPDs in Gianyar regency . The samples using proportionate stratified random sampling method . The analysis technique used is simple linear regression analysis. Based on the results of testing the hypothesis in mind that the principles of good corporate governance has a positive effect on the financial performance of LPDs in Ginyar regency, Bali Provinve.
Keywords: principles of good corporate governance , financial performance , CAMEL